The Values of Volunteering
XIV, 226 p.
Keywords: Volunteering is one of those phenomena which, despite the limited number of people actually involved in it, is seen as highly important for the proper functioning of society. In fact, volunteering and active participation in voluntary associations are considered to be key components of civil society; it is felt that they generate social cohesion and societal self-regulation as well as strengthening political democracy by developing individual citizenship and organizing countervailing powers. Issues such as these have gained momentum in recent years, especially since Putnam's publications in the 1990s on civic community and democracy in Italy and on the decline of social capital in the United States. However, interest in these issues in fact dates back to the time of the Civic Culture project carried out in the 1950s and 1960s by Almond and Verba, and even much earlier to Tocqueville's famous study Democracy in America in the 1830s. All of these studies, and many more, stress the importance of voluntary civic engagement for the development and maintenance of civilized societal cohesion and political democracy. This research tradition addresses volunteering as just one form of voluntary social and political involvement that might well be linked with other forms, such as passive and active membership of voluntary associations, incidental political activism, or individual involvement in public discourse. However, most studies on volunteering are written in another tradition that is more specifically directed toward direct helping behavior, service delivery, and unpaid work.